2019
DOI: 10.3390/cancers11101488
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling of Nrf2 Expression Promotes Mesenchymal State Maintenance in Non-Small Cell Lung Cancer

Abstract: Epithelial mesenchymal transition is a common mechanism leading to metastatic dissemination and cancer progression. In an effort to better understand this process we found an intersection of Nrf2/NLE2F2 (Nrf2), epithelial mesenchymal transition (EMT), and metabolic alterations using multiple in vitro and in vivo approaches. Nrf2 is a key transcription factor controlling the expression of redox regulators to establish cellular redox homeostasis. Nrf2 has been shown to exert both cancer inhibitory and stimulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Whilst ROS are necessary to initiate EMT, it is unclear to what extent they are required to maintain a mesenchymal phenotype. Consistent with ROS playing a role in initiation of EMT, treatment with the antioxidant NAC can antagonise stimulation of EMT by TGF-β in various cells types, including murine AML12 hepatocytes (Kim et al, 2019), human ARPE-19 adult retinal pigment epithelial cells (Yang et al, 2020) and human HCC4006 lung epithelial cells (Haley et al, 2019). Possibly more surprising is that in a stably gefitinib-resistant human PC-9 non-small cell lung cancer cell line, treatment with NAC has been reported to increase an epithelial-phenotype and decrease the mesenchymal-phenotype (Li et al, 2020), suggesting a relative absence of ROS may stimulate mesenchymal-to-epithelial transition (MET).…”
Section: F) Emt During Cancer Progression Entails Marked Changes In Redox Status and Tumor Cell Heterogeneitymentioning
confidence: 91%
See 1 more Smart Citation
“…Whilst ROS are necessary to initiate EMT, it is unclear to what extent they are required to maintain a mesenchymal phenotype. Consistent with ROS playing a role in initiation of EMT, treatment with the antioxidant NAC can antagonise stimulation of EMT by TGF-β in various cells types, including murine AML12 hepatocytes (Kim et al, 2019), human ARPE-19 adult retinal pigment epithelial cells (Yang et al, 2020) and human HCC4006 lung epithelial cells (Haley et al, 2019). Possibly more surprising is that in a stably gefitinib-resistant human PC-9 non-small cell lung cancer cell line, treatment with NAC has been reported to increase an epithelial-phenotype and decrease the mesenchymal-phenotype (Li et al, 2020), suggesting a relative absence of ROS may stimulate mesenchymal-to-epithelial transition (MET).…”
Section: F) Emt During Cancer Progression Entails Marked Changes In Redox Status and Tumor Cell Heterogeneitymentioning
confidence: 91%
“…Comparisons between epithelial-like human MCF-7 breast cancer cells and mesenchymal-like human MDA-MB-231 breast cancer cells revealed that the latter produce substantially higher levels of H 2 O 2 than the former (Lunetti et al, 2019). Moreover, HCC4006, A549 and H538 non-small cell lung cancer cell lines treated with TGF-β to induce a mesenchymal phenotype produce substantially higher levels of ROS than their non-treated epithelial counterparts (Haley et al, 2019). By contrast, breast cancer stem cells (BCSCs) with an epithelial-type morphology (i.e., E-BCSCs) have been reported to generate high levels of ROS, exhibit metabolic flexibility and possess heightened NRF2-regulated antioxidant defences necessary for survival, whereas BCSCs with a mesenchymal-type morphology (i.e., M-BCSCs) have low ROS levels, are dependent on glycolysis for energy, do not have high antioxidant defences, and do not require NRF2 for survival (Luo et al, 2018).…”
Section: F) Emt During Cancer Progression Entails Marked Changes In Redox Status and Tumor Cell Heterogeneitymentioning
confidence: 97%
“…Researchers have raised an interesting consideration regarding the changes in metabolism from primary tumor, migrating cells, and cells that colonize the metastatic niche, in which a sort of EMT-MET occurs. EMT and MET in metastasis formation is a theme that has been deeply discussed [ 187 ] and a deeper comprehension of the associated metabolic alterations could hopefully provide important insight to counteract cancer cell dissemination [ 188 ].…”
Section: Emt and Metabolism In Selected Cancersmentioning
confidence: 99%
“…390 In consistence with these, treatment of antioxidants, such as N-acetylcysteine (NAC), curcumin, resveratrol, has been shown to inhibit EMT in a variety of tumor cells. [391][392][393] It is worth noting that ROS also promote MET in cancer cells. For example, 2-deoxyglucose-induced ROS accumulation promotes the phenotype transition of mesenchymal breast cancer stem cells (CSCs) into epithelial breast CSCs.…”
Section: Regulation Of Emt By Redox Signalingmentioning
confidence: 99%